Humble Leaders and Innovative Behaviors, the Role of Psychological Empowerment - Ernawati Marinda Sagala; Adi Rahmat; Muhammad Rasyid Abdillah (SAINS ORGANISASI, 2023)
This research was conducted at PT. Gora Mandau Sawit with the aim of examining the role of psychological empowerment in mediating the influence of humble leaders on innovative behavior. Research population conducted by researchers are all employees of PT. Gora Mandau Sawit, totaling 100 people, using the total sampling method, the sample for this study was 99 people (minus the researchers). Analysis of the research data used descriptive statistics and verification analysis, as an analytical tool used the Structural Equational Model which was processed with SmartPLS2 Software. The results of the analysis prove that at PT. Gora Mandau Sawit, the more effective the humble leader, the more likely he is to increase innovative behavior, and the humble leader influences the innovative behavior of employees through the mediation of psychological psychological empowerment